Acute effects of smoking on the arterial function of young healthy smokers - Pereira, Telmo; Costa, Tatiana (My University, 2019)
Several studies have supported the idea that smoking induces changes with direct impact on endothelial function and arterial stiffness. The main purpose of this study was to assess the acute effects of smoking on vascular function in healthy young adults. METHODS: We designed a quasi-experimental study, including ninety participants aged between 18 and 25 years. Participants were divided into three groups: Active exposure group (AG) - 30 usual smokers; passive exposure group (PG) and non-exposure control group (CG), each including 30 non-smokers matched for age, gender and overall lifestyle. Heart rate (HR), brachial blood pressure (bBP), flow-mediated dilation (FMD), aortic pulse wave velocity (PWV) and carotid pulse wave analysis (PWA) were evaluated in two moments: baseline and 30 minutes after smoking exposition (AG and PG) or 30 minutes after the first evaluation (CG). RESULTS: Significant changes from baseline were observed only in the AG, with an increase in PWV, from 5.6 ± 0.7 m/s to 6.1 ± 0.2 m/s post-smoking (p = 0.040), and a decrease in FMD of about -5.7 ± 2.3% after smoking one cigarette (p < 0.001). A significant increase in brachial and central BP was also observed in the AG. A trend for increase in brachial and central BP, and decrease in the FMD was observed in the PG and no significant changes were depicted in the CG. CONCLUSION: Just one cigarette produces significant detrimental acute effects on the vascular endothelium and hemodynamic profile of healthy young short-term smokers. Changes are also observed, although to a lesser extent, in passive smokers.
Keywords: Smoking; Endothelial dysfunction; Arterial stiffness; Risk factors; Fumar; Disfunção endotelial; Rigidez vascular; Fatores de risco